Pengaruh Kinerja Perusahaan, Komite Audit Dan Pergantian Auditor Eksternal Terhadap Ketepatwaktuan Pelaporan Keuangan - Indah Suryani Mukhtar; Nurzi Sebrina; Erly Mulyani (Universitas Negeri Padang, 2019)
The aim of this research is to provide empirical evidence on : 1) The effect of profitability on timeliness of financial reporting, 2) The effect of leverage on timeliness of financial reporting, 3) The effect of audit committee on timeliness of financial reporting, 4) The effect of auditor’s independency on timeliness of financial reporting, and 5) the effect of auditor’s rotation on timeliness of financial reportingThis type of research is causative research. The population is the finance companies listed in Indonesian Stock Exchange for 5 years from 2013 to 2017. This sample selected by purposive sampling method and use 51 sample companies. Type of data used in the form of secondary data from www.idx.co.id and the another website that related with this research. The analysis technique uses a multiple linear regressions analysis.The results showed profitability has no effect of timeliness of financial reporting, leverage has negative significantly effect on timeliness of financial reporting, audit committee has positive significantly effect on timeliness of financial reporting, and rotation of external auditor has no positive effect on timeliness of financial reporting